How research data is cited in scholarly literature: A case study of HINTS. Issue 3 (4th January 2019) - Yoon, JungWon; Chung, EunKyung; Lee, Jae Yun; Kim, Jihyun
Abstract : This study investigated how Health Information National Trends Survey (HINTS) data from the U.S. National Cancer Institute (NCI) was cited in the scholarly literature. It addressed the following research questions: (1) What patterns of citations exist among authors of research articles using HINTS data? and (2) How is the citation format of HINTS data characterized? We collected scholarly articles that used HINTS data as primary or secondary data for analysis from Web of Science databases and HINTS publications on the NCI website. Among the resulting 250 articles, we identified citations to HINTS data themselves (data citations) and those to HINTS‐related documents (data‐related citations). Among the 250 articles, 156 articles (62.4%) cited HINTS data or HINTS‐related documents; only 29 articles (11.6%) cited HINTS data, while 127 (50.8%) cited HINTS‐related documents. Both data and data‐related citations increased over time. Data citation format varied, and 13 different compositions of citation elements were identified. Author, Title, and Location (URL) were common elements. The frequent use of URLs is undesirable due to URL instability. Furthermore, the data citations showed not only various compositions of citation elements but also ill‐defined element formats. Standardized citation formats are therefore needed.